TuberOus SClerosis registry to increAse disease awareness (TOSCA) Post-Authorisation Safety Study of Everolimus in Patients With Tuberous Sclerosis Complex - Kingswood, J. Chris; Belousova, Elena; Benedik, Mirjana P.; Budde, Klemens; Carter, Tom; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D'Amato, Lisa; d'Augères, Guillaume B.; de Vries, Petrus J.; Ferreira, José C.; et al. (Frontiers in Neurology, 2021)
This non-interventional post-authorisation safety study (PASS) assessed the long-term safety of everolimus in patients with tuberous sclerosis complex (TSC) who participated in the TuberOus SClerosis registry to increase disease Awareness (TOSCA) clinical study and received everolimus for the licensed indications in the European Union. The rate of adverse events (AEs), AEs that led to dose adjustments or treatment discontinuation, AEs of potential clinical interest, treatment-related AEs (TRAEs), serious AEs (SAEs), and deaths were documented. One hundred seventy-nine patients were included in the first 5 years of observation; 118 of 179 patients had an AE of any grade, with the most common AEs being stomatitis (7.8%) and headache (7.3%). AEs caused dose adjustments in 56 patients (31.3%) and treatment discontinuation in nine patients (5%). AEs appeared to be more frequent and severe in children. On Tanner staging, all patients displayed signs of age-appropriate sexual maturation. Twenty-two of 106 female (20.8%) patients had menstrual cycle disorders. The most frequent TRAEs were stomatitis (6.7%) and aphthous mouth ulcer (5.6%). SAEs were reported in 54 patients (30.2%); the most frequent SAE was pneumonia (>3% patients; grade 2, 1.1%, and grade 3, 2.8%). Three deaths were reported, all in patients who had discontinued everolimus for more than 28 days, and none were thought to be related to everolimus according to the treating physicians. The PASS sub-study reflects the safety and tolerability of everolimus in the management of TSC in real-world routine clinical practice.